Investigation of bovine interleukin-6 gene polymorphism and its association with Cryptosporidium infection in calves - MESHKAT, M; SHEMSHADI, B; AMINI, K (Journal of the Hellenic Veterinary Medical Society, 2022)
Interleukin-6 (IL-6) is associated with inflammatory diseases, but its connection with Cryptosporidium in Holstein calves remains unknown. This study aimed to investigate the effect of single nucleotide polymorphisms (SNPs) of IL-6 on the resistance and susceptibility to Cryptosporidium in calves and to prepare a phylogenetictree in order to show the relation between Cryptosporidium species. Seventy-two samples were studied from healthy and infected with Cryptosporidium calves and genotyped using the tetra amplification refractory mutation system (ARMS). The phylogenetic tree was constructed by the neighbor-joining method using the MEGA 7.0 software. The results showed a frequency of 76.40% for T allele and 23.60% for C allele in the healthy calves, while the results showed a frequency of 73.60% for T allele and 26.40% for C allele in calves infected with Cryptosporidium. The results did not reveal a significant difference between healthy and infectious animals according to the allele frequency (P=0.637). The phylogenetic tree demonstrated that C. parvum (HQ259589.1) with an 81% bootstrap were clustered with C. hominis (KM012041.1). The results also indicated that C. parvum (HQ259589.1) and C. hominis (KM012041.1) had a common ancestor with C. cuniculus. Additionally, C. andersoni(HQ259590.1) with an 88% bootstrap of support was placed in the same clade of C. muris (L19069.1), and both of them had a common ancestor with C. serpentis(KF240618.1). Further studies are required to investigate the relation between SNPs of IL-6 in other regions and the resistance or susceptibility to Cryptosporidium in calves.